The Secret Of “Circle” In Islamic Architecture - Sarand, Hossein Irani; Mohammadreza Pakdel, Fard; Taraf, Akbar Abdollah zadeh (The Turkish Online Journal of Design Art and Communication, 2016)
The Current study investigates the metaphorical properties and conceptual features of circler as one of the most significant geometric shapes in Islamic ornamentation as well as expression of its philosophical and symbolical aspects. Ornamentations in Islamic art and architecture covers the whole structure like a cloak, which aims at expressing unity, inspiring sacredness and eternity concept. Geometry is the key element of Islamic ornamentations and circle in this area has a high ranked position. In Islamic ideology, circle is the the only shape which symbolicaly can express the almighty God’s magnefisence.Islamic architecture has always reminds the viewr to the center and birthpoint of universe and highness of devine. . By analysis and knowledge of inherent unique capabilities of circle and its other geometric forms, i.e. sphere, ring and arches, somehow a proper field has been created for targeted and wakeful usage of it by architects. Based on the holistic research approach ,this paper follows theological argumentative procedure and it has been achieved by cultural- discursive system. This research reveals that it’s the shape of circle which can solely afford the expression of concepts in Islamic philosophy such as pure magnificent of God and perfection ,infinity and unity of the universe as well as light and the mystery in the world of symbols. Being converted from a geometric shape into artistic value, the circle is incorporated as a base for creation of ornamental geometric patterns and meaningful interlaced motifs and effects.
Keywords: Islamic architecture; circle; geometric patterns; philosophy of Islamic art; ornamentations; İslam mimarisi; daire; geometrik desenler; İslam sanatının felsefesini; süslemeler